TINGKAT KEPUASAN SISWA TERHADAP KUALITAS LAYANAN PADA LEMBAGA PENDIDIKAN ISLAM - KUSUMAWATI, DAHANI (TARLIM : JURNAL PENDIDIKAN AGAMA ISLAM, 2026)
Satisfaction is a primary indicator closely related to service quality. Schools, particularly Islamic educational institutions as providers of educational services, must be able to realize this satisfaction comprehensively through various services such as learning processes, a sense of safety, comfort, an enjoyable and inclusive environment, adequate facilities and infrastructure, counseling services, and other supporting services. SMA Muhammadiyah 3 Jember, as one of the Islamic educational institutions with the status of an excellent school in the Muhammadiyah Future School (MFS) program, aims to provide comprehensive services in order to achieve student satisfaction. This study aims to examine the level of student satisfaction with the quality of services at the Islamic educational institution, namely SMA Muhammadiyah 3 Jember. This research uses a quantitative approach with a survey research design. The instrument used is a questionnaire distributed to 131 student respondents. Data analysis was conducted using descriptive statistics. The results show that from all measured service indicators, 73 percent of students feel very satisfied, 25 percent feel satisfied, and the remaining 2 percent report being fairly satisfied. In conclusion, the level of student satisfaction with the quality of services at SMA Muhammadiyah 3 Jember as an Islamic educational institution is categorized as very satisfied, indicating that the quality of services provided by the school is very good.